Cross-sectional SWOT Analysis of BIM and GIS Integration - Glinka, Szymon (Geomatics and Environmental Engineering, 2022)
The integration of BIM (Building Information Modeling) and GIS (Geographic Information System) technologies allows for added value in many fields; starting from the construction industry to administrative operations. However, the issue of integration is currently quite challenging. This is due to the lack of consistency (inter alia, a lack of standards) in the integration of both technologies. It is the result of the different primary use of BIM and GIS. The use of BIM and GIS integration has great potential, especially in the construction industry. Therefore, it was decided to analyze the strengths and weaknesses of integration as well as the opportunities and threats in the future by performing a SWOT analysis. The analysis was performed cross-sectionally based mainly on the existing literature. Finally, six strengths, five weaknesses, five opportunities, and four threats were identified and described.